PENGEMBANGAN KURIKULUM TAHFIDZ DAN TAHSIN AL QUR’AN BERBASIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL ALAMIN (P5-P2RA) - Wahyuni, Iin; Fitri Puji Rahmawati; Anik Gufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The objective of this study is to describe the development of tahfidz and tahsin Al-Qur'an curriculum based on the Projek Penguatan Profil Pelajar Pancasila and Profil Pelajar Rohmatan Lil Alamin (P5-P2RA) at MI Muhammadiyah Kaliwuluh for the 2023/2024 academic year. The type of this study is Research and Development (R&D) with the Instructional Development Model (MPI). Tahfidz and Tahsin Curriculum Development Based on P5-P2RA contains components of the curriculum that can be used as a reference in program implementation. The implementation of Tahfidz and Tahsin Program based on P5-P2RA in MI Muhammadiyah Kaliwuluh can be an effective effort in building the character of Pelajar Pancasila and Pelajar Rahmatan Lil Aalamiin. It is supported by several factors, among others: P5-P2RA-Based Tahfidz and Tahsin Program encourages students to work together and collaborate with others.